2011
DOI: 10.1111/j.1863-2378.2011.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis and Tularaemia in Raccoons (Procyon lotor) of Larimer Country, Colorado

Abstract: Raccoons (Procyon lotor) are commonly implicated as carriers of many zoonotic pathogens. The purpose of this cross-sectional study was to look for Leptospira interrogans and Francisella tularensis in opportunistically sampled, free-ranging raccoons of Larimer Country, Colorado, USA. Sixty-five animals were included in the study and testing consisted of gross post-mortem examination, histopathology, and both immunohistochemistry and PCR for L. interrogans and F. tularensis. No significant gross lesions were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…In addition, wild animals, including raccoons and skunks, were identified as risk factors in PCR‐positive cats ( P ≤ .03). The former are also known maintenance hosts of the serovars Pomona and Bratislava and might indirectly infect cats . In fact, the population of raccoons in Quebec is massive, particularly in the Montérégie region where most of the cats were recruited, and raccoons are known carriers of Pomona and Bratislava .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, wild animals, including raccoons and skunks, were identified as risk factors in PCR‐positive cats ( P ≤ .03). The former are also known maintenance hosts of the serovars Pomona and Bratislava and might indirectly infect cats . In fact, the population of raccoons in Quebec is massive, particularly in the Montérégie region where most of the cats were recruited, and raccoons are known carriers of Pomona and Bratislava .…”
Section: Discussionmentioning
confidence: 99%
“…De Faria et al (2008) reported that up to 80.3% of Norway rats (Rattus norvegicus), a species that spread almost all over the globe, were culture positive and 68.1% were shown positive by antibody titers of at least 1:100 in a microscopic agglutination test (MAT). Other species of wild mammals have been detected as leptospiral carriers (Andreoli et al, 2014, Duncan et al, 2012, Pinna et al, 2012, Scialfa et al, 2013. In France, seropositivity rates were found to range from 31% in farmed American mink, 74% in wild European mink and up to 89% in stone martens (Moinet et al, 2010).…”
Section: Human Animal and Environmental Reservoirsmentioning
confidence: 99%
“…Several serologic surveys in the United States demonstrate that raccoons commonly have circulating antibodies to a number of L. interrogans serovars including grippotyphosa, autumnalis, hardjo, and icterohemorrhagiae (Junge et al, 2007;Raizman et al, 2009;Richardson and Gauthier, 2003). Some studies have confirmed nephritis in association with the bacteria by using PCR and immunohistochemistry, indicating that raccoons are susceptible to disease and do not simply serve as asymptomatic reservoirs (Duncan et al, 2012;Hamir et al, 2001;Koizumi et al, 2009). Leptospiral infections have also been reported in mongoose and genets, with L. interrogans serovar icterohemorrhagiae being the most commonly identified strain (Millán et al, 2009;Moinet et al, 2010).…”
Section: Bacteriamentioning
confidence: 99%